Dispatching for order-driven FABs with backward pegging. Issue 1 (31st December 2016) - Chung, Yong H.; Lee, S.; Park, Sang C.
Abstract: In this paper, a two-stage dispatching rule for the on-time delivery of an order-driven FAB is presented. Dispatching rules have a significant impact on the performance of FABs. Consequently, many such rules have been created, such as first in first out, earliest due data, operation due date, and critical ratio. Because these conventional dispatching rules make decisions only by considering the due date of each lot, they might not be suitable for dynamic order-driven FABs, for which it is very essential to monitor not only the due date of each lot but also the production rate of each step. In the first stage of the proposed two-stage dispatching rule, the production rate of each step is taken into account, and the due date of each lot is considered in the second stage. In this paper, the production rates of steps are computed by combining forward simulation and backward pegging. A simulation model, based on a wafer FAB data-set, has been developed, and simulation is conducted using commercial software SEEPLAN ® . The simulation results clearly show the advantages of the proposed dispatching rule over existing rules.